STRATEGI PENYEBARAN TRADISI ISLAM PADA MASYARAKAT JAWA - Sayfa Aulia Achidsti (IBDA` : Jurnal Kajian Islam dan Budaya, 2012)
This paper intends to present a brief understanding of the generalcondition of the relationship between religion and society in Indonesia.No longer any prophet as role model of Islam led to debate about Islam asa doctrine and religious practice, which is in the course of time the socialand political aspects are often greatly influenced its development. Thecondition is not as simple as when the Prophet was alive. Islam is movingdevelopments not only in the Middle East means the area has resulted inthe distance from the center of Islam. Contextualization in terms of thephysical form of Islam to be logical here, namely local community as abody, and Islam as the content.